TPACK : challenges for teacher education in the 21st century - Rocha, Aurora Maria Moreira da (2011)
In this paper we reflect on the impact of ICT in educational systems, and the importance of preparing Portuguese teachers to the challenges of the learning society. In order to contribute for the definition of a national program for the professional development of teachers in ICT, we present some international programs for the professional development of teachers in ICT discussing results on current implementation. We then present the recently launched Portuguese Plan of ICT Competences for teachers that define levels of digital literacy and certification. In order to add new insights into current discussion on the topic we present a review of literature on a theoretical framework that has shown effective for the integration of ICT into the classroom: the TPACK. Examples of successful experiences in different curricular areas already implemented and tested with will be presented and discussed in order to help Portuguese teacher educators in the design of activities to be carried out in education programs for in service teachers.